2013
DOI: 10.1155/2013/878237
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted Drug Resistance among People Living with HIV/Aids at Major Cities of Sao Paulo State, Brazil

Abstract: Human immunodeficiency virus type 1 (HIV-1) transmitted drug resistance (TDR) is an important public health issue. In Brazil, low to intermediate resistance levels have been described. We assessed 225 HIV-1 infected, antiretroviral naïve individuals, from HIV Reference Centers at two major metropolitan areas of Sao Paulo (Sao Paulo and Campinas), the state that concentrates most of the Brazilian Aids cases. TDR was analyzed by Stanford Calibrated Population Resistance criteria (CPR), and mutations were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…The overall moderate rate of TDR identified in the current study (11.2%) is in accordance with reports from other geographical regions in Brazil: 11.5% in the Northern Tocantins State; 10% in the Central Western Goiás State; 14.2% in the Southeastern São Paulo State, and 11% in the Southern Santa Catarina State [Cardoso et al, ; Carvalho et al, ; Graf et al, ; Ferreira et al, ]. Two recent multicenter surveys in Brazil have shown moderate levels of TDR [Inocencio et al, ; Sprinz et al, ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall moderate rate of TDR identified in the current study (11.2%) is in accordance with reports from other geographical regions in Brazil: 11.5% in the Northern Tocantins State; 10% in the Central Western Goiás State; 14.2% in the Southeastern São Paulo State, and 11% in the Southern Santa Catarina State [Cardoso et al, ; Carvalho et al, ; Graf et al, ; Ferreira et al, ]. Two recent multicenter surveys in Brazil have shown moderate levels of TDR [Inocencio et al, ; Sprinz et al, ].…”
Section: Discussionsupporting
confidence: 91%
“…The Brazilian AIDS epidemic is highly concentrated in the Southeast and South regions and several studies from these regions have reported TDR levels in different study groups [Inocencio et al, ; Sprinz et al, ; Sanabani et al, ; Ferreira et al, ; Pilotto et al, ; UNAIDS, ]. However, there is scanty data on the HIV‐1 molecular epidemiology in other regions away from the epicenter of the epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…These two mutations have been well characterised in the HIV-infected Brazilian population and are likely associated with the early high use of nevirapine based cART regimens for PMTCT purposes in southeastern and southern Brazil, from 1998 to 2001. [18][19][20] Although the Stanford algorithm employed in this study for characterisation of resistant mutations among ARV-naı¨ve subjects might tend to overestimate resistance, removal of questionable resistance mutations from the analysis did not change the number of naı¨ve subjects harbouring resistance to any class of ARVs. The moderate prevalence of ARV-resistance coupled with the high frequency of the aforementioned mutations which abrogate many commonly employed treatment plans, enforce the necessity to promote routine and universal ARV susceptibility testing to all Brazilian HIV-infected pregnant women for PMTCT purposes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Low to moderate levels of TDR have been reported in patients from the most densely populated southeast/south regions in Brazil. [4][5][6][7] However, there are very limited data from regions where the epidemic is growing, including Maranhão State in northeast Brazil, our study area, which has recently reported a 106.2% increase in AIDS cases rate. This is the first detailed molecular epidemiological investigation of TDR and HIV-1 genetic diversity among ARV-naive patients from Maranhão.…”
mentioning
confidence: 94%